The Transylvanian Dinosaur Museum project: The Contribution of GeoEcoMar to Valorize and Promote the Paleontological Heritage of Romania (Geo-Eco-Marina, 2018)
Interested in geoconservation, interpretation and promotion of the geological heritage, since 2014 NRDI GeoEcoMar is partner in the Transylvanian Dinosaur Museum project, aiming to reconstruct the late Cretaceous dwarf dinosaur fauna and ecosystems of the Hațeg Island in the Tethys Sea. The three, life-size museum quality dinosaur reconstructions, done in Alberta, Canada by world famous paleoartist Brian Cooley, were supported by GeoEcoMar in various ways. The institute sponsored the sculpture of the feathered theropod Balaur bondoc, offered incentives for the Kickstarter project “A Transylvanian dwarf dinosaur needs a ride home” which funded the travel from Calgary through Antwerp to Hațeg of the sauropod titanosaur Magyarosaurus dacus, offered logistic support for the Magyarosaurus journey in Romania and for the releasing from customs of the ornithopod Zalmoxes robustus. The workshops for children and exhibitions prepared reflect the interest of GeoEcoMar in geoheritage promotion through educational and outreach activities.
Keywords: Hațeg Geopark; dwarf dinosaurs; reconstruction; exhibition; workshop